Current and planned research for managing the risk of Xylella fastidiosa to New Zealand - Visnovsky, Sandra B.; Taylor, Robert K.; Teulon, David A.J. (New Zealand Plant Protection, 2019)
Xylella fastidiosa (Xf), a xylem-limited bacterium native to the Americas, has a devastating impact on many crops internationally. In California, Xf causes over USD 100 million in yearly losses to the grape industry and infects an estimated 200 million citrus trees in Brazil. More recently, Xf killed around one million olive trees on the Italian peninsula of Salento. Xylella fastidiosa is not known to be present in New Zealand. The glassy-winged sharpshooter (Homalodisca vitripennis), an important vector of Xf in California, is also not present in New Zealand. However, the meadow spittle bug (Philaenus spumarius), an important vector of Xf in Italy, is present. Many economically important horticultural, viticultural, agricultural, amenity and indigenous/native plant species, including taonga, are likely to be susceptible to Xf. Aspects of our research on Xf to understand the impact, reduce the likelihood of entry into New Zealand and/or minimising its impact in New Zealand will be presented. The research listed on the poster spans risk assessment, diagnostics, surveillance and biological control but could certainly be increased across the biosecurity continuum given the magnitude of the threat from Xf to New Zealand’s valuable plant systems.